Current Environmental Problems and Future Management in Komodo National Park - Sianipar, Imelda Masni Juniaty; Suryawan, I Wayan Koko (Journal of Sustainable Infrastructure, 2024)
Komodo National Park, an esteemed UNESCO World Heritage Site in Indonesia, is at a critical juncture, grappling with diverse environmental challenges. This study delves into these pressing issues, encompassing population pressure, destructive fishing practices, overfishing, introduction of non-native species, pollution, anthropogenic impacts, and wildlife hunting. Emphasizing the development of an adaptive program, the study synthesizes comparative literature and global conservation experiences to offer a nuanced understanding of these issues. The proposed program is holistic, aligning with broader conservation principles while addressing the park's specific needs. It encompasses strategies such as sustainable land use, resource management, tackling destructive fishing practices through stringent regulations and community engagement, and implementing quotas and seasonal closures to combat overfishing. Additionally, the study explores measures to control non-native species, reduce pollution, mitigate anthropogenic impacts on terrestrial habitats, and curb wildlife hunting. An integrated management approach, including regular scientific research, stakeholder collaboration, and monitoring, underpins these strategies. Drawing on successful global community-based resource management offers actionable insights for the future management of Komodo National Park.